Introduction - Šeškauskienė, Inesa; Ramonienė, Meilutė (Taikomoji kalbotyra, 2014)
This special issue of the journal Taikomoji kalbotyra/Applied Linguistics includes papers written on the basis of the presentations given at the International Applied Linguistics Conference Languages and People: Space, Time, Identity held in Vilnius University October 3-4, 2013. The Conference was organized by the Department of Lithuanian Studies of Vilnius University and the Lithuanian Association of Applied Linguistics (LITAKA). The total number of the Conference participants amounted to 60; they came from 12 countries: Australia, the Czech Republic, Estonia, France, Hong Kong, Italy, Latvia, Lithuania, Poland, Russia, United Kingdom and the United States of America. The plenary speakers of the Conference, world-known linguists Antonella Sorace (UK), Joseph Lo Bianco (Australia) and Mark Davies (USA), gave very impressive presentations on bilingualism and language acquisition, language planning and policy, language corpora as a powerful tool in language learning and teaching.
Keywords: none